Celluloid activist : the life and times of Vito Russo - Schiavi, Michael R. (Book collections on Project MUSE., 2011)
"Celluloid Activist is the biography of gay-rights giant Vito Russo, the man who wrote The Celluloid Closet: Homosexuality in the Movies, commonly regarded as the foundational text of gay and lesbian film studies and one of the first to be widely read. But Russo was much more than a pioneering journalist and author. A founding member of the Gay and Lesbian Alliance Against Defamation (GLAAD) and cofounder of the AIDS Coalition to Unleash Power (ACT UP), Russo lived at the center of the most important gay cultural turning points in the 1960s, 1970s, and 1980s. His life as a cultural Zelig intersects a crucial period of social change, and in some ways his story becomes the story of a developing gay revolution in America. A frequent participant at zaps and an organizer of Gay Activists Alliance (GAA) cabarets and dances which gave the New York gay and lesbian community its first social alternative to Mafia-owned bars. Russo made his most enduring contribution to the GAA with his marshaling of Movie Nights, the forerunners to his worldwide Celluloid Closet lecture tours that gave gay audiences their first community forum for the dissection of gay imagery in mainstream film. Biographer Michael Schiavi unravels Vito Russo's fascinating life story, from his childhood in East Harlem to his own heartbreaking experiences with HIV/AIDS. Drawing on archival materials, unpublished letters and journals, and more than two hundred interviews, including conversations with a range of Russo's friends and family, from brother Charlie Russo to comedian Lily Tomlin to pioneering activist and playwright Larry Kramer, Celluloid Activist provides an unprecedented portrait of a man who defined gay-rights and AIDS activism"--From publisher.